Water Inrush from Pregrouting Fractures Induced by Mining Activities and Its Engineering Control Method Optimization - Jianbo Li (Advances in Civil Engineering)
Water inrush accidents during coal mining still occur after reinforcement of fissured water bearing strata underlying coal seams through grouting, which seriously troubles field technicians. In order to further prevent the water inrush, especially the water inrush after grouting reinforcement, the grouting technique needs to be improved. Experimental design, theoretical analysis, and numerical simulation have been carried out in sequence. On the microscale level, the relationship between strains and water flow rate was analyzed through laboratory experiments; on the macroscale level, the propagation mechanism of grouting cracks resulting from the rock strata deformation during coal production was analyzed with rock beam theory, and then a new model of casing pipes preventing water inrush by controlling deformation of the floor rock strata is proposed. The laboratory test results show that the response of the radial strain and the water flow rate to mining operation is consistent and positively correlated and verify that it is feasible to reduce water inrush disaster by controlling deformation of the rock strata. The deformation governing equation of the casing pipes is deduced theoretically. At last, the numerical calculation was done to prove the effectiveness of controlling the floor rock strata deformation by the casing pipe group, which indicated that the displacement of the monitoring points after grouting is smaller than that before grouting practice. It is practicable to realize grouting technique optimization by the innovative adoption of the grouting casing pipes in the future.